The Influence of Personality and Emotional Intelligence on Work Fatigue with Nurse Performance as a Mediating Variable in Intensive Care Nurses at Gunung Jati Hospital, Cirebon City - Sri Atin; Kartono Kartono (Jurnal Medisci, 2026)
Background. Work fatigue is a problem that is often experienced by nurses, especially nurses who work in units with high levels of work pressure. Purpose. This study aims to analyze the influence of personality and emotional intelligence on nurses' work burnout and the role of nurses' performance in moderating these relationships. Method. This study uses a quantitative approach with a survey method, involving nurses who work at Gunung Jati Hospital, Cirebon City as respondents. Data was collected through questionnaires and analyzed using Structural Equation Modeling (SEM)-based path analysis techniques. Results. The results of the study showed that personality and emotional intelligence had a significant effect on nurses' work fatigue. In addition, nurse performance has been shown to play a role as a moderation variable that is able to weaken the negative influence of psychological factors on work fatigue. Conclusion. These findings affirm the importance of managing psychological aspects and improving nurse performance as a strategic effort to reduce the rate of work fatigue and improve the quality of health services.